الفتوحات ا إ لسلامية في عهد  عمر بن الخطاب الشام – مصر - الساسي, إلهام; لجدل الصيد, إلهام; الساسي, كوثر (جامعة الوادي university of eloued, 2015)
عمر بن الخطاب رضي الله عنو ىو ثاني الخمفاء ال ا رشدين عاش في طفولتو حياة مؤلمة و قاسية بسبب الفقر الذي كان يعيشو اضطر والده أن يقسو عميو بكل الأعمال الشاقة و ىذا ما جعل منو رجلا فذا و قويا لا يياب الموت يمد سيفو في كل معركة و لا يأبو لعدوه ميما كان عددىم لذلك لم يجد أبي بكر رضي الله عنو أحق منو ليخمفو من بعده و أخد منصب الخميفة الثاني، عمل في عيده الكثير من الانجا ا زت التي غيرت في مجال مسيرة الإسلام فقد قام بالعديد من الأعمال الميمة التي نيضت بالأمة الإسلامية من جديد و التي استعانوا بيا في السير إلى الدعوة الإسلامية. و من أىم أعمل الجبارة ىي الفتوحات الإسلامية التي قام بيا بمساعدة رفاقو فمم يأبيوا لا لمقتال و لا لمموت بذل وا في سبيل ذلك دمائيم و أرواحيم و فارقوا أىميم و أحباؤىم فقط من أجل الإصلاح و رفع البشر في أخلاقيم و أرواحيم و عقوليم لم يدخموا بالسيف والق وة بل دخموا بالمين و السمم لأن الإسلام دين سمم لا عنف و حرب فحاولوا أن ينشروا الدين الحنيف دون إيذاء البشر و رعبيم و قد كان ليم ما أ ا ردون و نجح او بعد جيد كبير و عظيم في فتح معظم البمدان العربية و بثوا فييا الدين الإسلامي و من ىاتو البمدان الشام و مصر Omar bin al-Khattab may Allah be pleased with him is the second khalifa, he lived his childhood life painful and harsh because of the poverty that had experienced forced by his father, that hardens upon all hard works and that's what made him an outstanding and strong man, he didn't fear death extends his sword in every battle, and does not care about the enemy regardless of their number, that's why make Abu Bakr may Allah be pleased with him take decision to give him the caliph after him, he made many achievements that have changed in the march of Islam and other important works that promoted the Muslim nation again and that They hired her to walk to the Islamic Dawa. The most important working mighty is the Islamic conquests carried out with the help of his comrades they did not fear to fight or to die they sacrifice their blood and their lives in order to reform and raise the human beings in their morals and their lives and their minds, they did not enter by the sword and strength but they entered leniency and in peace because Islam is a religion of peace not violence and war, they tried to spread the true religion without hurting humans and terrified them and they have done what they want by opening many different countries like Egypt and Sham. 
دعوة